Mundane: Thinking through All This Can Happen - Gareth Evans (The International Journal of Screendance, 2016)
What if… a text (Walser’s Walk) becomes image and sound and movement and new, and then becomes text again? This writing reflects on how images make history, now, on editing as placement and embodiment, on things bearing witness to things which must be borne witness to, and on rabbit holes of frames that might conjure up the world.
Keywords: image; sound; edits; All This Can Happen; Davies; Hinton